Por outras palavras (in other words) and digamos (so to speak): reformulation markers? - Ana Cristina Macário Lopes; Conceição Carapinha (Revista Galega de Filoloxía, 2017)
With this study, we aim to continue the study of the reformulative markers in European contemporary Portuguese (Lopes 2014). Two new discourse markers, por outras palavras and digamos, are syntactically, semantically and pragmatically described in this paper. The empirical data were colected from CETEMPúblico and the oral subcorpus of CRPC. Even though both discourse markers can be included in the paradigm of the reformulative ones, the study proves that digamos is not a prototypical member, given its productivity as a filler and a mitigation operator.